1
$\begingroup$

I am trying to find the integral of $$\int \tan^4 x \, \sec^6 x dx$$

I tried to rewrite as trig identities using $\sec^2 - \tan^2 = 1$ but that got me nowhere so I wrote it like this.

$$\int \frac{\sin^4x}{\cos^4 x} \frac{1}{\cos^6 x} dx$$

$$\int \frac{\sin^4x}{\cos^{10} x} dx$$

Then I use the idea that making u substitutions for cos will get rid of a power of sin so I just say that the power will go $4 3 2 1 0$ and I will get a $- + - + -$ sign change. I am not sure if this is correct or really how this works exactly but I did a few steps of it and it seemed to work correctly.

$$-1\int \frac{1}{u^{10}} dx$$

$$-1\int u^{-10} dx$$

$$-1 \times \frac{u^{-9}}{-9}$$

$$ \frac{u^{-9}}{9}$$

$$ \frac{\cos^{-9}}{9}$$

This is wrong and I am not sure why.

$\endgroup$
  • $\begingroup$ Did you see how your previous questions were edited? Do you mind using the same format? $\endgroup$ – Gigili Jun 3 '12 at 18:02
  • $\begingroup$ @Gigili What is the difference? $\endgroup$ – toby yeats Jun 3 '12 at 18:08
4
$\begingroup$

Your substitution is not correct. You should still still have a $\sin^3 x$ upstairs.

However when integrating a product of an even power of $\tan$ with an even power of $\sec$, you can do the following, which takes advantage of the facts that $\tan^2x+1=\sec^2 x$ and that the derivative of $\tan x$ is $\sec^2 x$:

First write $$\eqalign{\tan^4 x\,\sec^6 x&=\tan^4x\,\sec^4x\cdot \sec^2 x\cr &= \tan^4x \,(\sec^2x)^2\cdot \sec^2 x\cr &=\tan^4x \,(\tan^2 x+1)^2\cdot \sec^2 x.}$$ To evaluate the integral, set $u=\tan x$ (so that $du=\sec^2 x \,dx$).

$\endgroup$
3
$\begingroup$

Here is a relatively easier way. Remember that $\sec^2(x) = 1 + \tan^2(x)$. Hence the integral $$I = \int \tan^4(x) \sec^6(x) dx = \int \tan^4(x) \sec^4(x) \sec^2(x) dx\\ = \int \tan^4(x) \left(1 + \tan^2(x) \right)^2 \sec^2(x) dx $$ Let $\tan(x) = t$. Hence, $\sec^2(x) dx = dt$. Hence, we get that $$I = \int t^4 \left( 1+t^2 \right)^2 dt = \int t^4 \left( 1+2t^2 +t^4 \right) dt = \int \left(t^4 + 2t^6 + t^8 \right) dt\\ =\dfrac{t^5}{5} + \dfrac{2t^7}{7} + \dfrac{t^9}{9} + C$$ Hence, we get that $$I = \dfrac{\tan^5(x)}{5} + \dfrac{2\tan^7(x)}{7} + \dfrac{\tan^9(x)}{9} + C$$

$\endgroup$
0
$\begingroup$

No. You haven't done it correctly. Hint

  • $\tan^{4}(x) \cdot \sec^{4}(x) \cdot \sec^{2}(x)$.

  • $\sec^{4}(x) = (1+\tan^{2}{x})^{2}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.